REFERENCE, POLITENESS AND PARTICIPANT: COMPLAINTS IN LETTERS TO THE EDITOR IN DAILY GRAPHIC - Acheampong, Bliss (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
of Ghana. It seeks to discover the forms and modes of reference that writers use for the various participants in the LE. The paper brings together the politeness theory and Hymes’ (1972) categorization of participants in the complaint event. From closely analyzing fifty-three samples of LEs that were collected in over a period of four months, the study establishes that complainants of LE writers identify or refer to the participants either by a variety of specific terms (such as first personal pronouns and personal names) or by a range of plurality terms (such as the police, IMT staff), as this has implications for politeness. The findings support earlier findings by Hartford and Mahboob (2004), but also reveal a preponderance of generalized terms and no-mentions in reference to the parties responsible for either causing or redressing the grievance.